2016
DOI: 10.3390/ijms17091411
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 in Astroglial Cells in the CNS and Supporting Cells of Sensory Organs—A Comparative Perspective

Abstract: The main water channel of the brain, aquaporin-4 (AQP4), is one of the classical water-specific aquaporins. It is expressed in many epithelial tissues in the basolateral membrane domain. It is present in the membranes of supporting cells in most sensory organs in a specifically adapted pattern: in the supporting cells of the olfactory mucosa, AQP4 occurs along the basolateral aspects, in mammalian retinal Müller cells it is highly polarized. In the cochlear epithelium of the inner ear, it is expressed basolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 90 publications
(117 reference statements)
0
41
0
Order By: Relevance
“…Outside the central nervous system, AQP4 is expressed and localized at the basolateral membrane of epithelial cells in the kidneys, gastrointestinal organs, airways and skeletal muscles. However, the pathological changes seen in patients with NMOSD rarely occur in these AQP4‐expressing peripheral tissues . Recent studies suggest that the relatively low involvement and varying degrees of injury to peripheral organs may be related to the different distributions of the AQP4 isoforms and the expression of several membrane‐bound complement regulators in these organs .…”
Section: Cellular Expression and Tissue Distribution Of Aqp4mentioning
confidence: 99%
“…Outside the central nervous system, AQP4 is expressed and localized at the basolateral membrane of epithelial cells in the kidneys, gastrointestinal organs, airways and skeletal muscles. However, the pathological changes seen in patients with NMOSD rarely occur in these AQP4‐expressing peripheral tissues . Recent studies suggest that the relatively low involvement and varying degrees of injury to peripheral organs may be related to the different distributions of the AQP4 isoforms and the expression of several membrane‐bound complement regulators in these organs .…”
Section: Cellular Expression and Tissue Distribution Of Aqp4mentioning
confidence: 99%
“…In the human hippocampus, AQP4 has been found in the Cornu Ammonis (CA) and dentate gyrus (DG) areas. At the cellular and subcellular level, AQP4 is abundantly expressed in the plasma membrane of the astrocytes that sheathe the glutamatergic synapses and shows the highest expression in perivascular astrocytes, where it is localised to the plasma membrane of astrocytic end-feet at the glia limitans (Lee et al, 2004;Gleiser et al, 2016). AQP4 is co-localised with inwardly rectifying K + channels (Kir4.1) and glial K + uptake is attenuated in AQP4 knockout mice compared to wild-type, indicating a functional interaction (Padmawar et al, 2005;Binder et al, 2006Binder et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…AQP4 belongs to the CAQP subfamily and has been found in many organs since it was first discovered in the brain. AQP4 plays a role in maintaining the water balance of the central nervous system . According to studies using human tissue microarrays, AQP4 was found most frequently in the cerebral cortex, cerebellar cortex, ependymal cell layer, hippocampus, and spinal cord .…”
Section: General Characteristics Of Aquaporinsmentioning
confidence: 99%
“…According to studies using human tissue microarrays, AQP4 was found most frequently in the cerebral cortex, cerebellar cortex, ependymal cell layer, hippocampus, and spinal cord . In addition, it has been shown to be expressed in kidneys, salivary glands, and intestines as well as in the sensory organs retina, olfactory epithelium, and organ of Corti . Expression was found to be high in sensory cells, such as those associated with hearing, vision, and taste in zebrafish, but not in nonsensory cells .…”
Section: General Characteristics Of Aquaporinsmentioning
confidence: 99%